2007
DOI: 10.1002/mrc.2081
|View full text |Cite
|
Sign up to set email alerts
|

Purity analysis of hydrogen cyanide, cyanogen chloride and phosgene by quantitative 13C NMR spectroscopy

Abstract: Hydrogen cyanide, cyanogen chloride and phosgene are produced in tremendously large quantities today by the chemical industry. The compounds are also particularly attractive to foreign states and terrorists seeking an inexpensive mass-destruction capability. Along with contemporary warfare agents, therefore, the US Army evaluates protective equipment used by warfighters and domestic emergency responders against the compounds, and requires their certification at > or = 95 carbon atom % before use. We have inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
1
9
0
4
Order By: Relevance
“…The 13 C NMR spectrum shows one signal at 106.6 ppm, which is similar to those observed for a range of compounds, such as ClCN (95.5) and HCN (111.5 ppm),11 and features the expected 1:1:1 triplet pattern, which is due to coupling with 14 N ( I =1) with J ( 13 C– 14 N)=25 Hz (Figure 3). In the 14 N NMR spectrum (Figure 3), however, this coupling could not be observed, as the quadrupole moment of 14 N leads to signal broadening.…”
Section: Fundamental Vibrational Modes Of Nitryl Cyanidesupporting
confidence: 71%
“…The 13 C NMR spectrum shows one signal at 106.6 ppm, which is similar to those observed for a range of compounds, such as ClCN (95.5) and HCN (111.5 ppm),11 and features the expected 1:1:1 triplet pattern, which is due to coupling with 14 N ( I =1) with J ( 13 C– 14 N)=25 Hz (Figure 3). In the 14 N NMR spectrum (Figure 3), however, this coupling could not be observed, as the quadrupole moment of 14 N leads to signal broadening.…”
Section: Fundamental Vibrational Modes Of Nitryl Cyanidesupporting
confidence: 71%
“…At 0 8 8C, decomposition of 1 was observed within 2hand at À20 8 8Cwithin 8h,affording ahighly viscous black material. [55,56] Hence,f reshly prepared crystals or solutions were always needed for any further studies.…”
mentioning
confidence: 99%
“…Quantitative NMR analyses are typically reported for 'H, 4 -6 13 C 7-9 and 3 1p0-12 spectroscopy, however, quantitative spectroscopy for other nuclei 1 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] can also be found. Further, the accuracy and precision of NMR signal intensity measurements have recently been reviewed, 20 and more recently, Maniara et al 2 reported a systematic validation of the quantitative NMR method.…”
Section: Prefacementioning
confidence: 99%